Shaping Technique as a Media to Increase Independence in Adolescents with Diplegia Cerebral Palsy - Maftuhah Maftuhah; IGGA Noviekayatie (Proceedings of The ICECRS, 2020)
Teenager with diplegia cerebral palsy has poor ADL (Activity Daily Living) ability. This is due to that he doesn’t train his ability while at home because his family choose to give him full support by preparing all his needs. The goal of this researches is to change dependent behavior to more independent in his simple daily routine that related to optimum hand utilization and also ability to move independently. Researcher is using experimental method with case study approach. Researcher give behavioral therapy intervention (shaping) to improve level of independence of subject. Intervention was done in 5 session, including rapport, determined activity, activity training, intervention and evaluation. Intervention was done in 6 days doing observation and using target achievement activity checklist. Before intervention, subject always aided in daily living activity. After intervention, subject want and able to do simple daily activity such as eat, using and tidy up his clothes and also moved independently. The result of this researches show that shaping behavioral therapy can be used to improve level of independence in teenager with cerebral palsy diplegia.